18.3k views
2 votes
Please Help / Number 6 ( Look at the picture ) MY WORK HAS TO BE SHOWN TO GET FULL CREDIT

Please Help / Number 6 ( Look at the picture ) MY WORK HAS TO BE SHOWN TO GET FULL-example-1

1 Answer

2 votes

Answer:

y - 11/8

Step-by-step explanation:

The first step in simplifying the expression is to expand it.


(5)/(4)(y-1)-(1)/(8)(2y+1)=(5)/(4)y-(5)/(4)-(2y)/(8)-(1)/(8)

A bit of rearranging gives


((5y)/(4)-(y)/(4))-(5)/(4)-(1)/(8)

Now,


(5y)/(4)-(y)/(4)=(4y)/(4)=y

and


-(5)/(4)-(1)/(8)=-(10)/(8)-(1)/(8)=-(11)/(8)

therefore,


((5y)/(4)-(y)/(4))-(5)/(4)-(1)/(8)=y-(11)/(8)

Hence, our answer is


\boxed{y-(11)/(8)}

which can be written as


(1)/(8)(8y-11)\text{ }

User Xanagandr
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.